Collegial Environment Vitality - New York State Association of Two-Year Colleges, Inc.; Rinehart, Richard L.; New York State Association of Two-Year Colleges, Inc. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1982)
The Commission on Instruction of the New York State Association of Two-Year Colleges sponsored a competition which solicited papers on exemplary practices and procedures that improve the spirit of vitality and morale in two-year colleges. This special journal issue includes the brief papers accepted for the competition. After Richard L. Rinehart's introduction, Judith Byman and others discuss methods adopted at Monroe Community College to deal with retrenchment and declining faculty morale. Next, Dennis Callas outlines five factors necessary for improving the process of instructional strategy selection. Then, Frances C. D'Amico and Roberta S. Rosenbaum present information on Queensborough Community College's (QCC's) faculty advisement program designed to increase student retention. After articles by Barbara Davis on Onondaga Community College's faculty colloquium series on topics of current interest and by Imgard F. Karle on QCC's faculty development program, Willard Keane outlines an organizational development approach to stress management among administrators. Next, Arthur S. Oblas discusses faculty strategies for overcoming student passivity and self-defeating games. After Mark Peel's description of Delhi College's professional development grants program, Sally Walters focuses on efforts of the College of the Finger Lakes to promote college services and integrate part-time faculty and students into the fabric of the school. Finally, Mark Peel discusses ways of dealing with faculty and administrator anxiety. (HB)
Educational Dimensions, Special Issue No. 3.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrators; College Faculty; Community Colleges; Faculty Advisers; Faculty Development; Full Time Faculty; Instructional Innovation; Organizational Development; Part Time Faculty; Program Descriptions; Retrenchment; School Holding Power; Student Attitudes; Teacher Attitudes; Teacher Morale; Two Year Colleges; New York; Reports, Descriptive; Collected Works, Serials